Lung cancer, pulmonary emphysema and pleural effusion: An autopsy study - Marel, Miloslav; Koubkova, Leona; Kovarikova, Zuzana; Grandcourtova, Alzbeta; Petrik, Frantisek; Hroudova, Hana; Capkova, Linda; Kodet, Roman; Fila, Libor (Biomedical papers, 2015)
Objectives: To determine the exact incidence of lung cancer, pulmonary emphysema and pleural effusion we decided to carry out an autopsy study.Methods: In this autopsy study carried out over two years, we compared the results of autopsy findings with the clinical data in accompanying records of the deceased.Results: Among the 708 deceased subjects, there were 398 males and 310 females with a median age of 71 years. At autopsy, 55 cases of lung carcinoma (BCA) were found, of which 24 have not been identified during life (44%). Among the deceased with BCA, emphysema was also observed at autopsy in 40% of the cases. Pulmonary emphysema was described macroscopically in 28% of the full set of 708 deceased, whereas the accompanying records of the deceased described this condition in only 12% of the cases. Microscopic changes compatible with emphysema were identified in 54% of the examined lungs. Pleural effusions were described in the accompanying records of 13% of the deceased, while the autopsies showed this condition in 33% of the deceased. BCA was accompanied by effusion in 25% of the cases.Conclusions: The obtained results show that the studied conditions are present in more cases than are reported by clinicians. The study confirms the commonly accepted association between lung cancer and emphysema.
Keywords: autopsy pathology; lung cancer; emphysema; pleural effusion